Clopidogrel can be an effective complementary prophylactic for drug-refractory migraine with patent foramen ovale. (26th August 2020) - Guo, Yichen; Shi, Yujie; Zhu, Dan; Liu, Rui; Qi, Yi; Luo, Guogang
Abstract : The present study aims to determine the potential prophylactic effect of clopidogrel for migraine with patent foramen ovale (PFO) in patients who are poor responders to two or more common preventive medications. Migraineurs underwent contrast-enhanced transcranial doppler examination to confirm the presence of PFO and determine the right-to-left shunt degree. Clopidogrel 75 mg/day was added to the existing prophylactic regimen for 3 months and 6 months. The presence of PFO was found in 56.8% (151/266) of all patients with migraine and 70.2% (59/84) of migraine with aura (MHA), and among MHA a large shunt was observed in 36 patients. Twenty-six patients with drug-refractory migraine took clopidogrel 75 mg/day for 3 months. Compared with those at baseline, headache frequencies and attack durations were significantly lower (6.17±3.93/month (M) vs 3.28±2.67/M, p=0.003; 13.62±13.98/hour (H) vs 7.36±7.33/H, p=0.0049, respectively); visual analog scale scores and migraine disability assessment scores were also obviously decreased (6.32±1.97 vs 4.71±1.20, p<0.001; 22.14±7.13 vs 16.00±5.92, p=0.001, respectively). These improvements were maintained for 6 months in 12 patients. We concluded that PFO was closely correlated with migraine, especially in MHA. Clopidogrel could act as an effective complementary prophylactic for migraine with PFO in patients with poor response to routine prophylactics.